New additions of lichens from Assam, India - Behera, Prashant Kumar; Joseph, Siljo; Nayaka, Sanjeeva; Singh Chauhan, Rajveer (Plant Science Today, 2024)
An account of 7 lichen species new to lichen biota of Assam is presented. The species are Bactrospora paludicola, Buellia pleiotera, Byssolecania deplanata, Graphis urandrae, Gyalidea fritzei, Mycobilimbia philippina and Staurothele fissa. Among them, B. paludicola and G. fritzei are being reported for the first time from India. The lichen samples were collected from various protected areas of Assam and a detailed systematic account is provided.